2022
DOI: 10.1002/anie.202213462
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Ammonia Oxidation to Dinitrogen by a Nickel Complex

Abstract: We report a nickel complex for catalytic oxidation of ammonia to dinitrogen under ambient conditions. Using the aryloxyl radical 2,4,6‐tri‐tert‐butylphenoxyl (tBu3ArO⋅) as a H atom acceptor to cleave the N−H bond of a coordinated NH3 ligand up to 56 equiv of N2 per Ni center can be generated. Employing the N‐oxyl radical 2,2,6,6‐(tetramethylpiperidin‐1‐yl)oxyl (TEMPO⋅) as the H‐atom acceptor, up to 15 equiv of N2 per Ni center are formed. A bridging Ni‐hydrazine product identified by isotopic nitrogen (15N) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…In 2021, Peters et al described stepwise N 2 H 4 formation with a Ni­(II)–NH 2 radical . In 2023, Mock and co-workers developed a catalytic version with a half-sandwich Ni­(II) N-heterocyclic carbene (NHC) complex with hydrogen atom abstraction reagents . In 2021, MacFarlane et al studied AO on heterogeneous Cu(0) metal and ascribed the catalytic activity to an intermediary [Cu II (OH) 4 ] 2– ion .…”
Section: Artificial Ammonia Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Peters et al described stepwise N 2 H 4 formation with a Ni­(II)–NH 2 radical . In 2023, Mock and co-workers developed a catalytic version with a half-sandwich Ni­(II) N-heterocyclic carbene (NHC) complex with hydrogen atom abstraction reagents . In 2021, MacFarlane et al studied AO on heterogeneous Cu(0) metal and ascribed the catalytic activity to an intermediary [Cu II (OH) 4 ] 2– ion .…”
Section: Artificial Ammonia Oxidationmentioning
confidence: 99%
“…39 In 2023, Mock and co-workers developed a catalytic version with a half-sandwich Ni(II) Nheterocyclic carbene (NHC) complex with hydrogen atom abstraction reagents. 40 In 2021, MacFarlane et al studied AO on heterogeneous Cu(0) metal and ascribed the catalytic activity to an intermediary [Cu II (OH) 4 ] 2− ion. 41 Though Cu is nature's choice to oxidize ammonia in biological systems, it was not until recently that it gained wider attention.…”
Section: ■ Biological Ammonia Oxidationmentioning
confidence: 99%
“…We later reported catalytic NH 3 oxidation to N 2 by [Ru­(tetramesitylporphyrin)­(NH 3 ) 2 ] using organic aryloxy compounds as hydrogen atom abstraction (HAA) reagents . These HAA reagents have also been used for oxidation of M–NH 3 complexes with Cr, Mo, Mn, Os, and Ni complexes and have the potential to function as mediators that are regenerated at an electrode . Progress has also been made in homogeneous electrochemical ammonia oxidation using Mn, Fe, Cu, and Ru .…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to achieve more consistent results, we explored well-defined Ni complexes and were intrigued by reports of NHC-ligated Ni­(II) half-sandwich catalysts, which have recently been utilized for catalytic oxidative N–N coupling of ammonia to dinitrogen. These easily synthesized and air-stable complexes have been implicated to undergo hydride-mediated reduction to Ni­(I). , Additionally, the substituent cyclopentadienyl (Cp) ligand has demonstrated surprisingly facile equilibration among η 5 , η 3 , and η 1 binding modes, which we hypothesized could satisfy the previously observed requirement for a coordinatively unsaturated catalyst. , After evaluating a variety of Ni half-sandwich catalysts, we found that the use of 7a afforded a reproducible 61% yield of the desired product (entry 10). Exploration of solvent effects revealed that a 1:4 mixture of CH 2 Cl 2 /THF further improved the yield to 80% (entry 11).…”
mentioning
confidence: 99%